Placement Precision of Organic Fertilizer Based on Soil Conservation in Taro Cultivation - Andi Masnang; Asmanur Jannah; Dyah Budibruri Wibaningwati; Febi Nurilmala; Lany Nurhayati (The University of Lampung, 2022)
One of the things that are important to consider when fertilizing is how to place the fertilizer so that plants can consume nutrients efficiently. The research objective was to assess the precision of soil conservation based on fertilizer placement so that fertilizers could increase the production of taro effectively. This study applied four treatments, namely without fertilizer, placing manure in the planting hole, placing manure in the biopore, and placing manure on the borders. The three treatments were given 1 kg of goat manure. The treatment was performed with six replications. Harvesting is carried out in 8 months after planting. The results showed that the placement of manure on the borders was the most effective treatment with the highest yield of wet tubers of 21.4 Mg/ha and was not different from the treatment of manure in biopore 18.3 Mg/ha.This yield was different significantly as compared to that of resulted from treatments where fertilizer was placed in the planting hole (15.9 Mg/ha) or the production of taro without manure application (11.57 Mg/ha). Keywords: Organic fertilizers, production, soil conservation, taro